Trees for food and fodder - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
When farmers in northern Nigeria clear their fields for planting there are two medium-sized trees that are never cut down: the locust bean trees Parkia clappertonia and Parkia filicoidea. Scientists are now confirming what local farmers have long...